Mechanisms of Formation of Necessary Skills in Students through Clubs Organized in Schools - Zohidjonovna, Xusanova Feruza (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses such features as the targeted orientation of students to the profession through clubs, as well as effective work, as well as the growing demand for professional and spiritual qualities and competencies in young people.